Pine-Oak Type: A unique resilient global system with high potential for nature-based solutions - Surendra Pratap Singh; Donald B. Zobel (Ecological Indicators)
Distributed across all the continents of the Northern Hemisphere, Pinus (∼113 species) and Quercus (∼435 species) are among the most important forest forming genera of the planet. The cooccurrence of pines (Pinus species) and oaks (Quercus species), separated by ∼ 100 million years in the evolutionary history, and hence differing conspicuously in life history, morphology and adaptation to environment, has immense ecological importance. However, ecology of many species and several geographical areas has hardly been investigated. Here, we discuss why “pine and oak type” is an important ecological entity of global significance with regard to (i) evolutionary time scale, and (ii) diversification of the genera, (iii) environmental responses of species, and (iv) co-occurrence of pine and oak despite their contrasting responses to drought and fire. Furthermore, given their long term persistence, and resilience and successional linkage we have (v) discussed a few aspects of their potential for Nature based Solutions (NbS). While the pines’ basic strategy is to keep a ‘wide safety margin’, both in terms of hydraulic parameters and protection of stem with thick bark to deal with water stress and fire respectively, oaks depend on effective recovery after the damage caused by drought or/and fire. To achieve it, oaks’ strategy is to maximise resource (carbohydrate) capture by keeping stomata open in dry conditions and use resources to recover by resprouting. There is a need to extend research to many more species of pine and oak to understand this ecological system. Pine and oak forests have contributed to the sustenance of organic agriculture in several parts of Himalayas as an example, and hold potential for NbS in a changing world.